2018
DOI: 10.3389/fphar.2018.00140
|View full text |Cite
|
Sign up to set email alerts
|

Antihyperalgesic Properties of Honokiol in Inflammatory Pain Models by Targeting of NF-κB and Nrf2 Signaling

Abstract: The present study investigates the possible anti-nociceptive effect of intraperitoneal (i.p.) honokiol: a phenolic compound originally isolated from Magnolia officinalis, in acute and chronic inflammatory pain models. Doses of 0.1, 5, and 10 mg/kg honokiol were administered in carrageenan induced pain and the dose (honokiol 10 mg/kg i.p.) with most significant response among behavioral tests was selected for further experiments. The i.p. administration of honokiol inhibits mechanical hyperalgesia, mechanical a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
50
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(52 citation statements)
references
References 59 publications
2
50
0
Order By: Relevance
“…Firstly, Wang and Liu 37 reported that activation of NF-κB signaling contributed to the occurrence of inflammation-related IBS-diarrhea. In addition, recently, we detected that NF-κB signaling was also implicated in IBS-related hyperalgesia in an unpublished research, consistent with previous studies reporting that NF-κB signaling participated in the pain modulation in inflammatory diseases, 38 cancer, 39 and autoimmune diseases, 40 via the release of inflammatory cytokines such as IL-1β, IL-6, and TNF-α. Moreover, our findings indicate that the excitatory effect of CHT1 in GI motility is closely associated with increased ACh release.…”
Section: Discussionsupporting
confidence: 90%
“…Firstly, Wang and Liu 37 reported that activation of NF-κB signaling contributed to the occurrence of inflammation-related IBS-diarrhea. In addition, recently, we detected that NF-κB signaling was also implicated in IBS-related hyperalgesia in an unpublished research, consistent with previous studies reporting that NF-κB signaling participated in the pain modulation in inflammatory diseases, 38 cancer, 39 and autoimmune diseases, 40 via the release of inflammatory cytokines such as IL-1β, IL-6, and TNF-α. Moreover, our findings indicate that the excitatory effect of CHT1 in GI motility is closely associated with increased ACh release.…”
Section: Discussionsupporting
confidence: 90%
“…These results suggested that honokiol might suppress the FGF2‐FGFR1 autocrine loop signaling pathway by inhibiting the expression of FGF2.It has been reported that NF‐κB may serve as a transcription factor for the FGF2 gene, regulating the expression and release of FGF2 . In our investigation, we found considerable evidence that honokiol could inhibit the activation of the NF‐κB pathway . Hence, we infer that honokiol reduces the expression of FGF2 via the NF‐κB signaling pathway.…”
Section: Discussionsupporting
confidence: 58%
“…The mice were administered 25‐MHA (10 mg/kg, i.p) 40 min prior to the administration of CFA (20 μl/paw) and 1 h before the injection of carrageenan (100 μg/paw). Mechanical hyperalgesia in mice was determined using the Randall Selitto test according to the previously described methods (Khalid et al, ; Khan et al, ). Before the start of the test, the mice were placed in a quiet room for 15–30 min to acclimatise to the environment.…”
Section: Methodsmentioning
confidence: 99%